Analisis Tingkat Rawan Kekeringan Lahan Sawah dengan Pemanfaatan Penginderaan Jauh dan Sistem Informasi Geografis di Kabupaten Sragen Tahun 2014 - Dhani Susanto, Aditya; , Drs. H. Yuli Priyana, M.Si; , Agus Anggoro Sigit, M.Si, M.Sc (2015)
This research was conducted in the regency for 2014 aims to (1) determine the distribution of drought-prone level of rice field in the Sragen Regency in 2014 and (2) to analyze the dominant factors affecting level of drought prone rice field in the Sragen Regency. The method used in this research is quantitative method with the incorporation tiered Landsat 8 as primary data and secondary data on land use, slope, soil texture, soil solum and rainfall. Regency is the mapping unit, and the unit of analysis using land units. Determination of the field survey using stratified sampling method based on land units. The results from this study obtained map level drought-prone rice field. Rice field in Sragen has an area of 40 182 hectares. Level drought prone rice field area has a low percentage of 43.16% of the existing rice field and the majority are in the technical unit of irrigated rice field with a slope that is flat and smooth-textured soil. Spreading located in the District Sambungmacan, Ngrampal, Gondang, Sragen, Karangmalang, kedawung, Masaran, Sidoharjo and partly District of Sambirejo, Plupuh, and Tanon. Level drought prone rice fields were vast percentage of 30.99%, the majority located in the unit in the technical unit of irrigated rice field with flat to gentle slope and slightly rough textured, these classifications are in most sub-district Sumberlawang, Miri, Kalijambe, Gemolong, Tanon, Plupuh and Sambirejo. Level drought prone rice fields have a higher percentage of 25.85% area by land units making up the majority of rainfed manifold with slope variations that range from flat to moderately steep and rough texture of the soil and spreading predominantly located in the District Tangen, Gesi, Mondokan, Sukodono, Sumberlawang, and a small portion in the District Gemolong and Kalijambe. Factors which dominates the level drought-prone rice field land in Sragen is land use based on irrigation techniques and soil solum.